2023
DOI: 10.1007/s40615-022-01432-1
|View full text |Cite
|
Sign up to set email alerts
|

Black Mothers in Racially Segregated Neighborhoods Embodying Structural Violence: PTSD and Depressive Symptoms on the South Side of Chicago

Abstract: This study employs multi-level and mixed-methods approaches to examine how structural violence affects the health of low-income, single Black mothers. We use multilevel regression models to examine how feeling “trapped” in racially segregated neighborhoods with high levels of violence on the South Side of Chicago affects mothers’ ( N = 69) reports of posttraumatic stress disorder and depressive symptoms. The relationship between feeling “trapped” and variations in expression of mRNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Their exposome is full of various forms of toxins that foster chronic stress and worry in ways that negatively shape health outcomes. Such chronic stress exposure, as evidenced by increased PTSD symptoms for mothers who feel trapped in their neighborhood, demonstrates the extent to which persistent exposure to racial trauma/oppression is detrimental to the very lives of Black mothers, their children, and their communities [3,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their exposome is full of various forms of toxins that foster chronic stress and worry in ways that negatively shape health outcomes. Such chronic stress exposure, as evidenced by increased PTSD symptoms for mothers who feel trapped in their neighborhood, demonstrates the extent to which persistent exposure to racial trauma/oppression is detrimental to the very lives of Black mothers, their children, and their communities [3,29].…”
Section: Discussionmentioning
confidence: 99%
“…One in four Black women in the United States lives below the poverty line [4] and one third of urban Black women live in hypersegregated neighborhoods [5]. Women who live in hypersegregated neighborhoods experience higher levels of violence with more serious physical and mental health issues than women who do not reside in such communities [3,[6][7][8][9]. In Chicago, racialized health disparities are associated with a long history of racial trauma, including systematic hypersegregation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also provide possible mechanisms for how psychological stress gets "under the skin" to affect physical health as we also found that mothers who feel trapped in their neighborhood show a 50% reduction in the odds of high glucocorticoid receptor (GR) mRNA level (OR=0.50, p<0.001). (See Mendenhall et al, 2023 for full regression results). For future research we would like to include a control group, to better gauge the disparity for this population.…”
mentioning
confidence: 99%